2010
DOI: 10.1002/pssc.200983615
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation density assessment via X‐ray GaN rocking curve scans

Abstract: The line shape of X‐ray diffraction (XRD) rocking curves of GaN layers grown epitaxially on (0001) oriented sapphire substrates is analyzed. Measurements performed with double‐ and triple‐crystal setup show a q‐3 and q‐4 intensity decay, respectively, as expected for peak broadening dominated by randomly distributed dislocations. A model developed in [2], based on a restricted random dislocation distribution is fitted to the entire peak shape and used to extract dislocation densities and correlation lengths fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 7 publications
2
19
0
2
Order By: Relevance
“…(3), we estimate the dislocation density to be N TD E4.6 Â 10 9 cm À 2 in the reference c-GaN layer. This is consistent with an XRD analysis [19] and etch pit density measurements, both yielding a value of roughly 5 Â 10 9 cm À 2 . Nevertheless, a similar procedure cannot be applied for the m-plane GaN layer, as for nonpolar GaN layers, the relationship between N TD and lifetime was found to be extremely weak.…”
Section: Characterization Of Photoelectric Properties By Transient Grsupporting
confidence: 84%
“…(3), we estimate the dislocation density to be N TD E4.6 Â 10 9 cm À 2 in the reference c-GaN layer. This is consistent with an XRD analysis [19] and etch pit density measurements, both yielding a value of roughly 5 Â 10 9 cm À 2 . Nevertheless, a similar procedure cannot be applied for the m-plane GaN layer, as for nonpolar GaN layers, the relationship between N TD and lifetime was found to be extremely weak.…”
Section: Characterization Of Photoelectric Properties By Transient Grsupporting
confidence: 84%
“…In order to determine the dislocation density, analysis of the rocking curves shown in Figures 4 (a) -4(d) has been performed following the approach due to Kaganer et al [16,17]. This approach has been shown in previous works to yield very reliable estimates of dislocation density for GaN [18][19][20] and SiGe [21][22][23] epitaxial layers. Unlike in the more-widely-used Dunn and Koch method [35] (or the Williamson-Hall method [36]), which relies solely upon the FWHM value of a Gaussian distribution of the diffracted intensity, to determine the TDD by the Kaganer approach, the -rocking curves are fitted by [16] ( ) = ∫ (− 2 + ) cos( ) + ∞ 0 … … … (5) where and are the integrated peak intensity and the background intensity, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Here, we study the molecular-beamepitaxy (MBE)-growth of Ge1-xSnx layers on Ge/Si(001) substrates and investigate the threading dislocation densities (TDD) in these layers, by the approach developed by Kaganer et al [16,17]. We demonstrate that this high-resolution-X-ray-diffraction (HRXRD)-based technique, which has been successfully used to estimate dislocation densities in GaN [18][19][20] and SiGe [21][22][23] in previous works, also provides very reliable estimate of the same, for large area Ge1-xSnx epilayers. We observe that the relaxation of the Ge1-xSnx epilayers is predominantly driven by dislocations threading from the underlying Ge buffer layers.…”
Section: Introductionmentioning
confidence: 95%
“…It was reported that oxygen atoms can penetrate even deeper regions of the heterostructure via diffusion along dislocations [14]. Typical defect densities of our samples are in the range of several 10 9 cm -2 [15]. Oxygen atoms could have locally damaged the heterointerface, resulting in the observed mobility deterioration.…”
Section: Methodsmentioning
confidence: 94%